Properties and Storage Stability of O/W Emulsion Replaced with Medium-Chain Fatty Acid Oil - Kupongsak Sasikan; Sathitvorapojjana Saruda (Polish Journal of Food and Nutrition Sciences)
The properties and changes of an o/w emulsion(mayonnaise) as affected by the replacement of long-chain fatty acid oil with medium-chain fatty acid oil were studied. Different ratios of coconut oil (CNO) and rice bran oil (RBO) (0:100, 10:90, 20:80, 30:70 and 40:60 (v/v)) were blended as the oil base for the study. The highest replacement of RBO with CNO in an o/w emulsion that could be achieved with minimal change of sensory properties was 30%. The Emulsion Stability Index and oil-phase crystallisation temperatures of mayonnaise with RBO alone and with 30% CNO replacement did not change when stored at 30±2°C for 4 weeks. The droplet size of the mayonnaise containing only RBO increased, possibly due to droplet coalescence. In contrast, the droplet size of the mayonnaise with CNO:RBO=30:70 did not change during storage.